A case of gemcitabine-induced thrombotic microangiopathy in a urothelial tumor patient with a single kidney - Hyunjin Ryu; Eunjeong Kang; Seokwoo Park; Sehoon Park; Kyoungbun Lee; Kwon Wook Joo; Hajeong Lee (The Korean Society of Nephrology, 2015)
Thrombotic microangiopathy (TMA) is a rare complication of gemcitabine treatment. A 55-year-old man with a history of urothelial cancer underwent right ureteronephrectomy and palliative chemotherapy. The patient presented with dyspnea, generalized edema with foamy urine, and new-onset hypertension with acute kidney injury (AKI). Although AKI with oliguria was evident, thrombocytopenia and hemolytic anemia were not overt. To determine the cause of rapidly progressive azotemia, kidney biopsy was performed despite a single kidney and revealed chronic TMA. Microangiopathic hemolytic anemia and thrombocytopenia developed after renal biopsy. Diagnosed as gemcitabine-induced TMA, gemcitabine cessation and active treatment including steroids, plasmapheresis, and rituximab were carried out, but the patient׳s condition progressed to a dialysis-dependent state. Gemcitabine-induced TMA is often difficult to diagnose because of its variable clinical course. Therefore, heightened awareness of this potentially lethal complication of gemcitabine is essential; renal biopsy may be helpful.